Psychiatric Evaluation of Chronic Diarrhea: A Case Report - Moien Kardoust; Pouria Yazdian-Anari; Mostafa Nasiripour; Reza Bidaki (Baqiyatallah University of Medical Sciences, 2016)
Introduction: Diarrhea is one of the most common symptoms treated in general practice and gastroenterology. An estimated 1.7 billion cases of diarrhea are reported annually. Anxious and emotional persons are more sensitive to digestive problems. Anxious persons may feel their heartbeat and perceive their intestinal motility and spasm, and this may cause them more concern. Case Presentation: In this case report, a 31-year-old woman with chronic diarrhea and a stressed psyche is presented so as to emphasize the combination of organ disorders and psychiatric moods. Conclusion: Patients suffering from chronic and persistence gastrointestinal disease should be evaluated by a psychiatrist. Psychotherapy and psych pharmacotherapy can greatly help the treatment of somatic complaints of these patients.